Imaging Predictors for Endovascular Recanalization of Non-acute Occlusion of Internal Carotid Artery Based on 3D T1-SPACE MRI and DSA - Chao, Liu; Qingbin, Meng; Haowen, Xu; Shanshan, Xie; Qichang, Fu; Zhen, Chen; Sheng, Guan (Frontiers in Neurology, 2021)
Objectives: To investigate the predictive factors for successful recanalization based on digital subtraction angiography and three-dimensional T1W sampling perfection with application-optimized contrasts using different flip angle evolutions (3D T1-SPACE) high-resolution magnetic resonance imaging (MRI) signal features. Methods: Consecutive internal carotid artery occlusion cases with ipsilateral ischemic stroke refractory to therapy who visited our institution between February 2017 and August 2020 were retrospectively analyzed. Epidemiology, symptomatology, imaging morphology on angiography and MRI, peri-procedural complications, technical success rate, and follow-up results were summarized. Factors related to technical success were analyzed using univariate and multivariate analyses. Results: In total, 75 cases (53 men, mean age 57.51±9.71) were included. The total successful recanalization rate was 72.00% (54/75), with a complication rate of 13.33% (9/75). Through multivariate analysis, first ischemic stroke in <3 months (OR: 2.57; 95% CI: 1.13–4.58), tapered stump (OR: 4.31; 95% CI: 1.37–13.55), reversed flow of the ophthalmic artery (OR: 2.99; 95% CI: 1.06–8.49), high intraluminal signal on unenhanced T1 SPACE sequence (OR: 16.15; 95% CI: 3.40–76.72), no vessel wall collapse (OR: 17.00; 95% CI: 3.57–81.02), short occlusion length (OR: 9.87; 95% CI: 2.09–46.64), and primary occlusion site at the cervical internal carotid artery (OR: 8.42; 95% CI: 1.04–68.19) were associated with successful recanalization. Conclusion: Besides traditional features such as short ischemic event time, tapered stump, and distal ICA reconstitution by the ophthalmic artery, our study demonstrates that luminal and mural changes determined by 3D SPACE high-resolution MRI could also predict successful endovascular recanalization.